2017
DOI: 10.3390/nano7100287
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Probe for Detection of Aluminum (III) Ions Using Surface Functionalized Gold Nanoparticles

Abstract: A simple green route has been developed for the synthesis of casein peptide functionalized gold nanoparticles (AuNPs), in which casein peptide acts as a reducing as well as the stabilizing agent. In this report, AuNPs have been characterized on the basis of spectroscopic and microscopic results; which showed selective and sensitive response toward Al3+ in aqueous media, and Al3+ induces aggregation of AuNPs. The sensing study performed for Al3+ revealed that the color change from red to blue was due to a red-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
(65 reference statements)
2
10
0
Order By: Relevance
“…Comparing the obtained LOD and LOQ values for the proposed method with those reported by other authors who used different AgNPs/AuNPs-based sensors for detecting aluminum ions (Table 3) [4,29,[45][46][47][48], we found that the citrate+PVP-AgNPs-based sensoring system provides lower limits of detection and quantitation. Only a sensor using AgNPs capped with 8-hydroxyquinoline-5-sulfonate offers lower LOD.…”
Section: Analytical Study Of the Citrate+pvp-agnps:al Interactionsupporting
confidence: 63%
See 1 more Smart Citation
“…Comparing the obtained LOD and LOQ values for the proposed method with those reported by other authors who used different AgNPs/AuNPs-based sensors for detecting aluminum ions (Table 3) [4,29,[45][46][47][48], we found that the citrate+PVP-AgNPs-based sensoring system provides lower limits of detection and quantitation. Only a sensor using AgNPs capped with 8-hydroxyquinoline-5-sulfonate offers lower LOD.…”
Section: Analytical Study Of the Citrate+pvp-agnps:al Interactionsupporting
confidence: 63%
“…selective detection of Al(III) [26,27,47]. The obtained LOD values in these studies are of the same order as the LOD of the proposed system.…”
supporting
confidence: 61%
“…In cross-linking strategies, AuNP aggregation is induced by the controlled assembly of ligand-functionalized AuNPs with the formation of intermolecular bonds (such as H-bonding or hydrophobic interactions), which overpower the interparticle repulsive forces (such as electrostatic repulsion). Peptide-functionalized AuNPs have been developed as biological recognition probes for cross-linking methods in colorimetric diagnoses [31,32,33,34,35]. Chandrawati et al utilized peptide-conjugated AuNPs for monitoring the concentration of blood coagulation Factor XIII, which requires thrombin and Ca 2+ for activation [36].…”
Section: Aggregation-based Colorimetric Assaysmentioning
confidence: 99%
“…Sensing study in the presence of ionic compound and at different pH is also important to validate the applicability of the sensor under different conditions 63 . We studied the effects of different ionic strength levels and various pH values on bio-interfacial sensing of pesticide.…”
Section: Effects Of Ionic Strength and Ph On Detection Of Chlorpyrifosmentioning
confidence: 99%